Morphological, histopathological and molecular characterization of Thelohanellus pathankotensis n. sp. (Cnidaria: Myxosporea: Myxozoa) infecting an Indian minor carp, Labeo dero Hamilton, 1822 from a cold water wetland in Punjab (India) - Kaur, Harpreet; Gupta, Aditya (Zootaxa, 2017)
A new myxobolid, Thelohanellus pathankotensis parasitizing gill lamellae and caudal fins of the Indian minor carp Labeo dero has been described using light microscopy, histopathology and molecular analyses. The fish host was collected from a cold water wetland, Ranjit Sagar Wetland, Punjab, India located 32 ̊ 26 ̍ 30 ̎ N Latitude and 75 ̊ 43 ̍ 30 ̎ E Longitude. The prevalence of infection was 30%. The plasmodia were located in the gill lamellae and the caudal fins were cylindrical and whitish, 0.8–1.0 mm in size containing about 150–300 myxospores. The myxospores had a mean length of 9.70 ± 0.50 µm, width 3.85 ± 0.27 µm, mean length of polar capsule 3.0 ± 0.15 µm, width 2.68 ± 0.08 µm. The 18S rDNA nucleotide with 1098 bp of Thelohanellus pathankotensis n. sp. (accession number KU516661) clustered phylogenetically with other myxozoan parasites, with the species most closely related was T. sp. PBS- 2015 with 92% homogeneity and T. boggoti with 98% homogeneity. The intensity of infection or the mean abundance was determined by the gill plasmodial index (GPI) based on the number of countable plasmodia. The myxospores of the present species differed from others previously described infecting the hosts of family Cyprinidae, same tissue location and geographical location.